Brain fingerprints along the language hierarchy - Zhang, Juan; Zhuang, Liping; Jiang, Jiahao; Yang, Menghan; Li, Shijie; Tang, Xiangrong; Ma, Yingbo; Liu, Lanfang; Ding, Guosheng (Frontiers in Human Neuroscience, 2022)
Recent studies have shown that the brain functional connectome constitutes a unique fingerprint that allows the identification of individuals from a group. However, what is the information encoded in the brain that makes us unique remains elusive. Here, we addressed this issue by examining how individual identifiability changed along the language hierarchy. Subjects underwent fMRI scanning during rest and when listening to short stories played backward, scrambled at the sentence level, and played forward. Identification for individuals was performed between two scan sessions for each task as well as between the rest and task sessions. We found that individual identifiability increased along the language hierarchy. Further analyses suggest that the high-order functions of the brain are more important than the low-order functions in identifying individuals, mainly due to a high degree of inter-subject variability. However, the task-independent neural processes seem to contribute the most to distinguish individuals. These findings advance the understanding of the source of brain individualization and have potential implications for developing robust connectivity-based biomarkers.